MULTIFUNCTIONALITY OF AGRICULTURE: A BRAZILIAN PERSPECTIVE/ Multifuncionalidade da agricultura: uma perspectiva brasileira/ Multifuncionalidad de la agricultura: una perspectiva brasileña - Schnitman, Tarita (REVISTA NERA, 2020)
Earlier international studies on multifunctional agriculture question rural development and show a new direction to rural areas. This approach is conceptualised as a counter to larger industrial agriculture and integrates social, economic, environmental preservation, productive and cultural values to sustain farming communities among traditional farmers. Brazilian researchers have previously argued for a four-pillar model of rural development to be incorporated to the concept of multifunctional agriculture. This paper presents a framework to investigate this theoretical approach. It presents a Brazilian case study among the Quilombola community of Mandira-Brazil and how it fulfils the four-pillar model. Results show exemplary protection of their cultural and biophysical territory and recognition of their traditional ways by the State, the ability to sustain livelihoods over time, but keeping the youth engaged is a challenge. The case study reveals unique Brazilian lenses towards the approach.